Power and exploitation in the Czech lands in the 10th-12th centuries : a Central European perspective - Petráček, Tomáš, 1972- (East Central and Eastern Europe in the Middle Ages, 450-1450,, 2017)
Power and Exploitation in the Czech Lands in the 10th-12th Centuries: A Central European Perspective offers a unique analysis of the history of early medieval Czech society. It draws new attention to the role of serfdom and slavery in the early period of the Přemyslid dynasty in the Czech lands, and the organization of land and property access and ownership. The provocative conclusions reached by the author in this study shed new light on the oldest period of Czech history. Petráček analyses these issues comparatively, also taking into account Poland and Hungary; this is an approach unique to this book.